Risk Factors for Developing Severe Acute Kidney Injury in Adult Patients With Refractory Postcardiotomy Cardiogenic Shock Receiving Venoarterial Extracorporeal Membrane Oxygenation. Issue 8 (August 2020) - Lepère, Victoria; Duceau, Baptiste; Lebreton, Guillaume; Bombled, Camille; Dujardin, Olivier; Boccara, Lucile; Charfeddine, Ahmed; Amour, Julien; Hajage, David; Bouglé, Adrien
Abstract : Objectives: Postcardiotomy cardiogenic shock occurs in 2–6% of patients undergoing cardiac surgery, and 1% of cardiac surgery patients will require mechanical circulatory support using venoarterial extracorporeal membrane oxygenation. Acute kidney injury is a frequent complication in this population and negatively impacts the survival. We aimed to determine whether the timing of extracorporeal membrane oxygenation implantation influences the renal prognosis of these patients. Design: Retrospective observational cohort study between January 2013 and December 2016. Setting: An 18-bed surgical ICU in a university hospital. Patients: A total of 4, 796 consecutive adult patients who underwent cardiac surgery were included in the study, and 347 (7.2%) were assisted with venoarterial extracorporeal membrane oxygenation for refractory postcardiotomy cardiogenic shock. The patients who died during the first 48 hours after venoarterial extracorporeal membrane oxygenation implantation were excluded. The complete-case analysis included 257 patients. Interventions: None. Measurements and Main Results: The primary outcome was the occurrence, within 10 days following the venoarterial extracorporeal membrane oxygenation implantation, of a stage 3 acute kidney injury defined by the Kidney Disease: Improving Global Outcomes group. One hundred sixty-nine patients (65.7%) presented with a Kidney Disease: Improving Global Outcomes stage 3 acute kidney injury; 14 patients (5.4%) died before the end of the follow-up period, without developing the primary outcome. Ninety-two percent of patients with Kidney Disease: Improving Global Outcomes 3 acute kidney injury received renal replacement therapy, for a median duration of 7 days (3–16 d). Late implantation of venoarterial extracorporeal membrane oxygenation was independently associated with an increased risk of Kidney Disease: Improving Global Outcomes stage 3 acute kidney injury (odds ratio, 2.81 [95% CI, 1.31–6.07]; p = 0.008). The other factors associated with Kidney Disease: Improving Global Outcomes stage 3 acute kidney injury were preoperative left ventricular ejection fraction (odds ratio, 1.03 [95% CI, 1.01–1.05]; p = 0.007), intraoperative plasma transfusion (odds ratio, 1.13 [95% CI, 1.02–1.26]; p = 0.022), increased bilirubinemia level (odds ratio, 1.013 [95% CI, 1.001–1.026]; p = 0.032), and increased creatinine levels (odds ratio, 1.012 [95% CI, 1.006–1.018]; p < 0.001) on the day of implantation. Conclusions: Significant kidney dysfunction is particularly frequent in patients with refractory postcardiotomy cardiogenic shock assisted with venoarterial extracorporeal membrane oxygenation. Early implantation of extracorporeal membrane oxygenation may help prevent acute kidney injury. Abstract : Supplemental Digital Content is available in the text.